2013
DOI: 10.2119/molmed.2013.00140
|View full text |Cite|
|
Sign up to set email alerts
|

CB2 Receptor Deficiency Increases Amyloid Pathology and Alters Tau Processing in a Transgenic Mouse Model of Alzheimer’s Disease

Abstract: The endocannabinoid CB 2 receptor system has been implicated in the neuropathology of Alzheimer's disease (AD). In order to investigate the impact of the CB 2 receptor system on AD pathology, a colony of mice with a deleted CB 2 receptor gene, CNR2, was established on a transgenic human mutant APP background for pathological comparison with CB 2 receptor-sufficient transgenic mice. J20 APP (PDGFB-APPSwInd) mice were bred over two generations with CNR2 -/-(Cnr2 tm1Dgen /J) mice to produce a colony of J20 CNR2 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
1
8
2
Order By: Relevance
“…The degree of Iba-1 staining observed in the brains of APP/PS1*CB2 À/À mice suggested reduced microgliosis in the absence of CB2. This is in contrast to data presented by Koppel et al (Koppel et al, 2013) that demonstrated enhanced levels of Iba1 staining in CB2 À/À mice using a different (J20 APP) genetic model of AD. Unfortunately, this study did not establish baseline Iba1 levels in CB2 À/À and CB2 þ/þ mice, data that would be of importance based on our observations that at baseline CB2 À/À mice presented increased levels of Iba1 staining.…”
Section: Discussioncontrasting
confidence: 99%
“…The degree of Iba-1 staining observed in the brains of APP/PS1*CB2 À/À mice suggested reduced microgliosis in the absence of CB2. This is in contrast to data presented by Koppel et al (Koppel et al, 2013) that demonstrated enhanced levels of Iba1 staining in CB2 À/À mice using a different (J20 APP) genetic model of AD. Unfortunately, this study did not establish baseline Iba1 levels in CB2 À/À and CB2 þ/þ mice, data that would be of importance based on our observations that at baseline CB2 À/À mice presented increased levels of Iba1 staining.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, studies performed with late-symptomatic mice after CB2R deletion show contradicting results. Koppel et al reported an enhanced number of plaque-associated microglia in late-symptomatic mice after CB2R deletion accompanied by enhanced levels of soluble Aβ 42 levels and Aβ plaques [72]. In contrast, our study on latesymptomatic mice showed decreased levels of Aβ plaques.…”
Section: Alzheimer's Diseasecontrasting
confidence: 89%
“…In line with this finding, treating rats suffering from vascular dementia with HPβCD/BCP, a CB2R agonist, upregulated CB2R expression in the hippocampus and improved long-term spatial memory [130]. Moreover, as mentioned above, many different reports investigated the CB2 receptor in the context of AD and showed that the modulation of this receptor can influence learning and memory [51,72,73,131].…”
Section: Neuroinflammation and Cognitionmentioning
confidence: 53%
“…Recent in vivo studies in animal models of AD demonstrated an ameliorating effect of CB2 receptor agonists on cognitive deficits in these mice that was associated with decreased microglial reactivity, reduced expression of pro-inflammatory cytokines [ 78 , 79 ] and some decreases in Aβ accumulation after longer periods of treatments [ 79 ]. Genetic ablation of CB2 receptors in amyloid-producing mice resulted in opposing but significant effects on Aβ plaque load in different models [ 80 , 81 ] indicating that effects of CB2 receptors is likely to depend of the stage of amyloidosis and other factors.…”
Section: Discussionmentioning
confidence: 99%